Calorimetry Study of Coconut Husk Biofuel - Amran, Azyan Izzati; Embong, Zaidi (Enhanced Knowledge in Sciences and Technology, 2024)
Malaysia is looking into biofuels from coconut husk biomass as a sustainable and environmentally friendly alternative to fossil fuels. This research contributes to the country’s biomass energy sector and understanding renewable energy sources. The coconut industry in Malaysia has generated a significant waste issue due to the accumulation of coconut husks in landfills. Biofuel production from these husks presents a promising solution, reducing waste, developing renewable energy, and offering alternatives to fossil fuels. This study produced biomass pellets from coconut husks with the help of kerosene, petrol, and diesel as additives. Coconut husks were analysed using SEM-EDX and FTIR to assess their suitability for biomass pellet production. The Q-values of coconut husk pellets soaked in flammable additives were compared. SEM analysis revealed a rough and porous surface with 53.08% carbon and 44.72% oxygen, while FTIR analysis indicated that the functional group for all additives mainly consists of hydroxyl and double bonds in coconut husk pellets, while kerosene, petrol, and diesel showed varying combinations of C-O, C=C, and C-H stretches. A comparison of the combustion test for all pallets with different additives shows the highest Q-values by diesel. Thus, the use of diesel is more predominant for biofuel additives than kerosene and petrol.